Estimation of root and shoot growth of selected grass species on the basis of seedling characterization - Dziamski , Andrzej; Stypczyńska , Zofia; Żurek, Grzegorz (Plant Breeding and Seed Science, 2012)
Our study was designed to describe possibilities to estimate above- and below ground biomass of selected grass species by means of seedling development. Festuca arundinacea Schreb., Festuca rubra L., Lolium perenne L., Poa pratensis L., Koeleria macrantha (Ledeb.) Schultes, Deschampsia caespitosa (L.) P.B. were used in our experiment. On the basis of observations and measurements, differences between species, cultivars and ecotypes were described. Significant and positive correlation was found between root: shoot ratio at seedling phase and at mature plants.